2013
DOI: 10.1021/jp4016678
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Study of Superaromaticity in Cycloarenes and Related Coronoid Hydrocarbons

Abstract: Recently synthesized septulene is a unique cycloarene molecule in that no macrocyclic conjugation circuits can be chosen from the π-system. This molecule has essentially no superaromatic stabilization energy (SSE) and can be viewed as an ideal nonsuperaromatic macrocycle. SSEs for kekulene and other cycloarenes are also very small. In these hydrocarbons, a macrocycle formed by fused benzene rings effectively suppresses not only the aromaticity inherent in macrocyclic (4n+2)-site conjugation circuits but also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 72 publications
(209 reference statements)
0
82
0
Order By: Relevance
“…Our method for calculating SSE for macrocyclic π-systems is outlined below. 31,111,113 As an example, we evaluate SSE for kekulene (71). There are two types of circuits in 71: local circuits that do not enclose the inner cavity and macrocyclic ones that enclose the inner cavity.…”
Section: Superaromatic Stabilization Energy For Macrocyclesmentioning
confidence: 99%
“…Our method for calculating SSE for macrocyclic π-systems is outlined below. 31,111,113 As an example, we evaluate SSE for kekulene (71). There are two types of circuits in 71: local circuits that do not enclose the inner cavity and macrocyclic ones that enclose the inner cavity.…”
Section: Superaromatic Stabilization Energy For Macrocyclesmentioning
confidence: 99%
“…Before moving to the other super-ring 1,30-33 structures (3-7) depicted in Figure 2, we just observe in passing that the structures 1 and 2 (which, so far as we know, are hypothetical) whose current maps have just been presented in Figure 3, are formally related -by the suppression of two (structure 1) or four (structure 2) protons and the concomitant addition of one (structure 1) or two (structure 2) carbon-carbon bonds -to the well-known and characterised 54,55 planar condensed, benzenoid hydrocarbons ovalene 54 (8) and circumanthracene 55 (9), respectively; the HLPM topological current-maps of these structures -which, it should be noted, are not actually 'super-ring' ones 1,[30][31][32][33] -are presented in Figure 4. The topological ring-current intensities in ovalene (8) The peripheral rings in 8 and 9, like their counterparts in 1 and 2, do (as expected) bear avowedly diamagnetic ring-currents of the size routinely encountered in the condensed, benzenoid hydrocarbons.…”
Section: Structuresmentioning
confidence: 99%
“…11,12 The present authors have applied this technique to a wide variety of extant and hypothetical conjugatedsystems, 1,[13][14][15][16][17] primarily in order to test the so-called 'Annulene-Within-an-Annulene (AWA) Rule' 1,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] for what have been described as 'super-ring' structures. 1,[30][31][32][33] A general super-ring conjugated hydrocarbon is illustrated in Figure 1 (which is taken from Ref. 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As ar ing moiety for aC 60 planet, pconjugated macrocycles have been occasionally utilized because of the large attractive interactions between psystems. [5][6][7] Yamago et al reported that [10]CPP (diameter 1.38 nm) selectively formed acomplex [10]CPP'C 60 among aseries of CPPs. [4] Recently,c yclo-p-phenylenes (CPPs) and related cycloarylenes were extensively studied as hoop-shaped p-conjugated molecules.…”
mentioning
confidence: 99%